Autologous stem cell regeneration therapy: a new hope for diabetes mellitus patients with periodontal defects : Terapi regenerasi autologus stem sel: suatu harapan baru bagi penderita diabetes melitus dengan defek periodontal - Puspitasari, Rachmawati Dian; Gani, Asdar (Makassar Dental Journal, 2024)
Several studies have been conducted on the use of autologous stem cells derived from the patient's own body as a therapeutic agent to increase the speed of healing and regeneration of periodontal defects due to periodontitis, including in patients with sys-temic diseases such as diabetes mellitus (DM). This literature review discusses the application and clinical effectiveness of auto-logous stem cells as regeneration therapy in DM patients with periodontal defects, the long-term effects and advantages and disadvantages of this regeneration therapy. This literature search is based on electronic data such as Pubmed, Wiley, Google Schoolar using several keywords. Periodontal ligament stem cells are adult stem cells that can be applied directly to repair perio-dontal defects. Direct local injection of stem cells may be an effective approach for periodontal regeneration in patients with DM. It is concluded that stem cells have the potential to be used in tissue regeneration and engineering. Some of the main advanta-ges of stem cells are their high differentiation ability and proliferation rate, relatively simple extraction and culture for use in auto-logous cell therapy in DM patients with periodontal defects.